2014
DOI: 10.1016/j.ijgo.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of postabortion contraception, prioritizing long‐acting reversible contraceptives, in the principal maternity hospital of Gabon

Abstract: a b s t r a c t a r t i c l e i n f oKeywords: DMPA FIGO initiative Gabon Long-acting reversible contraceptives Postabortion contraception Prevention Unsafe abortion A prospective, descriptive, analytic study was conducted at the Centre Hospitalier de Libreville in Gabon between February and September 2013 to evaluate acceptance of long-acting reversible contraceptives (LARC) and depotmedroxyprogesterone acetate (DMPA) following abortion. Women received counseling on the combined oral pill, DMPA, copper intrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Nine publications, summarized in Table 2, concerned contraceptive counseling and provision following birth, abortion or miscarriage [16][17][18][19][20][21][22][23][24]. A major effort to provide postpartum IUD services in six countries, three in Asia and three in Africa, involved 330 hospitals in India and 78 health facilities (mainly hospitals) in the other countries.…”
Section: Postpartum and Postabortion Initiativesmentioning
confidence: 99%
“…Nine publications, summarized in Table 2, concerned contraceptive counseling and provision following birth, abortion or miscarriage [16][17][18][19][20][21][22][23][24]. A major effort to provide postpartum IUD services in six countries, three in Asia and three in Africa, involved 330 hospitals in India and 78 health facilities (mainly hospitals) in the other countries.…”
Section: Postpartum and Postabortion Initiativesmentioning
confidence: 99%
“…Several authors have thus demonstrated in developing countries, that clandestine abortion rate was higher for low socioeconomic patients. 6,9,10 Sociodemographic characteristics of our population confirmed a real need for contraception and the IUD is a suitable solution.…”
Section: -9mentioning
confidence: 54%
“…In one study of women ages 18-35, ambivalence regarding contraception use was linked to lower rates of contraception use (hence, higher risk for pregnancy and subsequent abortion) (Neustadt, Holmquist, Davis, & Gilliam, 2011). In other studies outside of the U.S., the majority of women who received post-abortion counseling were either unaware of modern contraceptive methods or were not using them at the time of their pregnancy (Ceylan, Ertem, Saka, & Akdeniz, 2009;Mayi-Tsonga, Obiang, Minkobame, Ngouafo, Ambounda, & DeSousa, 2014). However, following counseling, the majority of them accepted and used contraception at follow-up.…”
Section: Discussionmentioning
confidence: 99%